2015
DOI: 10.17957/tpmj/15.2998
|View full text |Cite
|
Sign up to set email alerts
|

Post Hemorrhoidectomy Pain Relief; Outcome of Local Anesthesia

Abstract: The aim of my study is to evaluate post-operative pain relief on patients who had hemorrhoidectomy. Materials and Methods: 300 patients who had hemorrhoidectomy were divided equally in to three groups, according to anesthesia type, group 1 (local anesthesia and sedation), while spinal anesthesia was group 2 and general anesthesia was considered to be group 3. Pain relief, post-operative complications, hospital staying time were measured and compared between the three groups. Period: Study was performed between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Our pilot study and a previous study [ 18 ] showed that the mean pain VAS score at 12 h was 5 (standard deviation [SD]: 3.5) in patients with hemorrhoidectomy under the spinal anesthesia. Utilizing α = 80% and β = 0.05, a 2-tailed analysis showed that we needed 49 patients/group for a reduction in pain intensity by 40% in the case of patients with hemorrhoidectomy under PNB with deep sedation.…”
Section: Methodsmentioning
confidence: 64%
“…Our pilot study and a previous study [ 18 ] showed that the mean pain VAS score at 12 h was 5 (standard deviation [SD]: 3.5) in patients with hemorrhoidectomy under the spinal anesthesia. Utilizing α = 80% and β = 0.05, a 2-tailed analysis showed that we needed 49 patients/group for a reduction in pain intensity by 40% in the case of patients with hemorrhoidectomy under PNB with deep sedation.…”
Section: Methodsmentioning
confidence: 64%